Analyzing The Optimal Leadership Style To Enhance Organizational Commitment In Student-Composed Startup: An Ethnographic Study of Asa Cerra - Kristarno, Regatta Odyssy; Wisesa, Anggara (Integrasi Sains Media, 2024)
Employees' decisions and actions have a significant impact on organizational performance. How a company treats its employees can benefit or harm the organization. Research indicates that employees with high organizational commitment contribute to better business outcomes. Leaders and managers play a crucial role in fostering this commitment by ensuring employees understand their roles, receive the necessary support, and recognize how their work contributes to the organization's success. However, a one-size-fits-all leadership approach is ineffective; leadership styles must be tailored to the organization's needs. In startups like Asa Cerra, a student-based healthy food technology company, each team member's contribution is crucial for rapid innovation. Asa Cerra faces frequent delays and underperformance, suggesting a decline in team commitment, which is essential for success. This study aims to identify the optimal leadership style for Asa Cerra to enhance organizational commitment. Using an ethnographic research design, data were collected through participant observation, in-depth interviews, and auto-ethnography from key informants, including team leaders and members. The analysis revealed that Asa Cerra's current leadership employs pace-setting and affiliative styles. While these styles have benefits, they fail to meet the co-founders' aspirations for stronger organizational commitment. The study suggests that combining coaching and democratic leadership styles could better enhance commitment. These styles align well with team members' expectations and address the limitations of the current pace-setting and affiliative approaches. By adopting coaching and democratic leadership, Asa Cerra can improve team commitment, leading to better performance and innovation.